A Rare Case of HHV-8 Associated Hemophagocytic Lymphohistiocytosis in a Stable HIV Patient - Nonso Osakwe; Diane Johnson; Natalie Klein; Dalia Abdel Azim (Case Reports in Infectious Diseases)
Background. Hemophagocytic lymphohistiocytosis (HLH) is a rare condition associated with viral infections including HIV. Cases have been reported mainly in advanced HIV/AIDS. This is a rare case that reports HLH associated with human herpes virus-8 (HHV-8) associated multicentric Castleman disease in a stable HIV patient. Case Presentation. A 70-year-old Asian male patient with history of stable HIV on medications with CD 4 cell count above 200 presented with cough and fever and was initially treated for pneumonia as an outpatient. Persisting symptoms prompted presentation to the hospital. The patient was found to have anemia which persisted despite repeated transfusion of packed red cells. A bone marrow biopsy to investigate anemia revealed hemophagocytosis. A CT scan revealed multiple enlarged lymph nodes and hepatosplenomegaly. An excisional lymph node biopsy revealed HHV-8 associated multicentric Castleman disease. The patient deteriorated despite initiation of treatment. Conclusion. HLH can occur at any stage of HIV, rapid diagnosis to identify possible underlying reactive infectious etiology and prompt initiation of treatment is crucial to survival.